«I am the one who knocks»: the motif of the double in "Breaking Bad" - Sánchez López, Fernando (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Among the unfathomable multiplicity of variables regarding the motif of the double, the most profoundly analyzed variation is intended to be the one related to an interior double and its identitary problem, a splitting of personality close to psychoanalytic notions about repressed traits of the human mind. In the present essay, after introducing some of its most paradigmatic instances, both in literature and cinema, the case study will be the television series Breaking Bad. Examining its protagonist, Walter White, and his alter ego Heisenberg, allows drawing some conclusions, both individually and contextually. The motif, as shown in Breaking Bad, seems to separate itself from the previous examples of the double, and becomes something admirable, attractive, close to our reality in comparison with the gothic, paranormal and uncanny aura of its precedents.